Analisis Penggunaan Metode MFCC Dalam Mendeteksi Emosi pada Musik Indonesia - Eka Wijaya, I Komang Sutrisna; Putri, Luh Arida Ayu Rahning (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 4 (2023): JNATIA Vol. 1, No. 4, Agustus 2023, 2023)
This research aims to develop a method for detecting emotions in Indonesian music using the MFCC method. The MFCC method is used to identify emotions in music by measuring acoustic features of music, such as tempo, pitch, and intensity. The study uses a dataset of 40 Indonesian music samples from various regions, which are analyzed to detect emotions. The confusion matrix is used to calculate the precision of emotion prediction. The results show that the MFCC method is effective in detecting emotions in Indonesian music. The research also highlights the importance of using a representative dataset to improve the accuracy of emotion identification in music. This study provides insights into the challenges and opportunities of using the MFCC method for emotion detection in Indonesian music.